Pengaruh Capital Adequacy Ratio Dan Non Performing Loan Terhadap Return On Asset Pada PT Bank Tabungan Negara (Persero) Tbk Periode 2012-2021 - Dilla Setiawati; Nina Shabrina; Muhamad Nurhamdi; Rita Satria (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the influence of the Capital Adequacy Ratio and Non-Performing Loans, both partially and simultaneously, on Return on Assets at PT Bank Tabungan Negara Tbk for the 2012-2021 period. This research method uses quantitative methods. The population in this research comes from the financial reports of PT Bank Tabungan Negara Tbk for the period 2012-2021 or for 10 years. The data analysis used includes the classical assumption test, simple linear regression test, multiple linear regression test, coefficient of determination test, partial test and simultaneous test. Data processing uses SPSS 26 software. Based on the t test, it can be seen that the Capital Adequacy Ratio partially influences Return on Assets, this is proven by the results of tcount (3.874) > ttable (2.3060) and the significance level is 0.06. Non-Performing Loans partially have a significant effect on Return on Assets, as evidenced by tcount (5.200) > ttable (2.3060) and a significance level of 0.001. And simultaneously the Capital Adequacy Ratio and Non-Performing Loans have an influence on Return on Assets, this is proven by the Fcount result of 15.980, while the Ftable can be searched for a statistical table of 0.05 and the Ftable is 4.46 (15.980 > 4.46) and the level of significance 0.002. The magnitude of the variable influence value is determined by Adjusted R2 = 0.820 then (KD = R2 x 100% = 0.820 x 100% = 82%).